Romance and Sexual Harassment at the Workplace Environment - Góralewska-Słońska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The purpose of this article is to present the problem of flirting and romance in the workplace, especially the consequences of sexual harassment. This paper presents the development of the organizational climate creating by flirting and romance at work. It also presents the issue of sexual harassment by defining the concept, forms and types. The study identifies the determinants of sexual harassment related to the organization. The article is also a theoretical basis for the research on the behaviours associated with the perception of flirting and sexual harassment by employees.